On organizational learning - Argyris, Chris (Blackwell Pub. OxfordGB, 1999)
Reviews literature on both the learning organization and, organizational learning. Focuses on organizational learning and provides insights into the causes of errors and how to correct them. Examines barriers to organizational learning and suggests human resource activities to reduce them. Looks at how using scientific approaches may inhibit actionable knowledge.